2011
DOI: 10.1162/glep_a_00069
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Global Fisheries Management: Linking Issues to Protect Ecosystems or to Save Political Interests?

Abstract: This article explores the conditions under which regional fisheries management organizations (RFMOs) adopt climate actions. I test a series of hypotheses to explain when RFMOs move beyond their classic management approaches—assignment of property rights, catch limits, and gear restrictions—to include climate change in their research and management plans. I introduce a new data set that compares fisheries-climate linkages since 1992 in all available RFMO annual reports and meeting minutes. The analysis reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The acceptance of best practice scientific advice in the face of economic interests has been problematic [55], with some RFBs following scientific advice 39% of the time or less [72]. While RFBs are addressing the wider domains of sustainability and biodiversity in management [73], the political pressures in shaping scientific advice to suit the agenda of members [74] or, as Axelrod notes, to maintain the status quo [75] is likely to be accentuated as fisheries are affected by climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptance of best practice scientific advice in the face of economic interests has been problematic [55], with some RFBs following scientific advice 39% of the time or less [72]. While RFBs are addressing the wider domains of sustainability and biodiversity in management [73], the political pressures in shaping scientific advice to suit the agenda of members [74] or, as Axelrod notes, to maintain the status quo [75] is likely to be accentuated as fisheries are affected by climate change.…”
Section: Discussionmentioning
confidence: 99%
“…included climate change in their research and management plans). He found that member countries were more apt to favour climate action not when it aligned with scientific recommendations, but rather when it coincided with avoiding catch regulations (Axelrod ). Also to circumvent catch regulations, O'Leary et al .…”
Section: Factors That Influence Fisheries Management Decisionsmentioning
confidence: 99%
“…included climate change in their research and management plans). He found that member countries were more apt to favour climate action not when it aligned with scientific recommendations, but rather when it coincided with avoiding catch regulations (Axelrod 2011). Also to circumvent catch regulations, O'Leary et al (2011) found that European Union Fisheries Ministers engage in competitive bargaining driven by immediate national interest when setting total allowable catch (TAC) regulations.…”
Section: Factors That Influence Fisheries Management Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests major ecological disturbances, particularly as we move beyond 2 °C of warming, whereby social ecological systems may transform into new, unanticipated states [5]. Meanwhile, fishery decline and species loss is already proving to be a major issue, with the majority of the world's fish stocks being maximized [6] and regional fishery policies not being enforced [7]. For many small-scale fishers, pressure on fish stocks and coastal resources has increased, while overall incomes and employment has declined, further marginalizing often impoverished households [8].…”
Section: Introductionmentioning
confidence: 99%